Big change, little change?: punctuation increments and multi-layer institutional change for English local authorities under austerity - Gardner, Alison (Taylor and Francis, 2017)
This paper draws on new institutionalist theories to consider how we might characterise the process and outcomes of change occurring in English local government as a result of the UK’s austerity policies. It uses national and local empirical data to argue that changes are best understood as multi-layer processes, whereby radical ‘punctuated’ shifts in national funding can be mitigated to incremental adjustments in service delivery at a local level. However, the paper also suggests that the incremental appearance of change may be temporary, and that diminishing institutional resilience and emergent discursive shifts potentially prefigure a paradigm change in local governance. Hall’s (1993) framework of policy change is used to assess the extent of change to date.